I have to solve the following equation:
I changed the first equation to y=9-x to solve for y. I got x(9-x)=54 and then 9x-x^2=54. I then changed 9x-x^2= 54 to -x^2 +9x-54=0. I got stuck around here, can someone explain...
Algebra - Reiny, Friday, January 2, 2009 at 3:28pm
It is a good idea to have your equations start with a positive square term, so switch all the signs
x^2 - 9x + 54 = 0
This equation does not have a real solution, if you want the imaginary values of x, use the quadratic formula.
YOu can see intuitively that there cannot be a real answer.
both the sum and the product are positve, so both x and y must be positive.
just mentally form some ordered pairs (x,y) which add up to 9.
No way will the product reach 54, the largest product you would get is (4.5)(4.5) or 20.25
Algebra - Damon, Friday, January 2, 2009 at 3:28pm
from the second equation say y = 54/x
then in the first
x + 54/x = 9
x^2 -9 x + 54 = 0
this quadratic has only complex roots
x = 9/2 +/-(1/2) sqrt(-135)
= 9/2 +/- (3/2) sqrt (-15)